Development and validation of a bioanalytical method by LC‐MS/MS for the quantification of the LAFIS 10 – an antimalarial candidate – and its pharmacokinetics first evaluation. (23rd October 2014) - Laureano, J. V.; Barreto, F.; Gnoatto, S.; Tasso, L.; Dalla Costa, T.; de Araujo, B. V.
Abstract A rapid and highly sensitive method by LC‐MS/MS was developed and validated for the quantification of an antimalarial candidate (LAFIS10) in rat plasma using dexamethasone as internal standard (IS). The chromatographic separation was performed with a Poroshell 120 EC‐C18 column. The mobile phase consisted of water (A) and acetonitrile (B), both containing 10 m m of ammonium formate and 0.1% formic acid, delivered in the form of elution gradient. The LAFIS10 was monitored using an electrospray ionization interface operating in the positive mode in multiple reaction monitoring mode, monitoring the transitions 681.47 → 538.2 for LAFIS10 and 393.20 → 355.30 for the IS. The flow rate was 500 μL/min. The column temperature was kept at 40 °C and the injection volume was 2 μL. The lower limit of quantification was of 10 ng/mL and linearity between 10 and 1000 ng/mL was observed, with an R2 > 0.99. The accuracy of the method was >90%. The relative standard deviations intra‐ and interday were <8.80 and <6.37%, respectively. The method showed sensitivity, linearity, precision, accuracy and selectivity required to quantify LAFIS 10 in preclinical pharmacokinetic studies according to criteria established by the US Food and Drug Administration and European Medicines Agency. Copyright © 2014 John Wiley & Sons, Ltd.